2013
DOI: 10.1039/c3mb70151d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, design and synthesis of new heteroaryl ethylenes active against the MCF-7 breast cancer cell-line

Abstract: A dataset of 50 compounds was used to generate a QSAR model and to design 9 new heteroaryl ethylenes. These compounds were synthesized, tested in vitro and a significant agreement with in silico predictions observed. Studies using Laser Scanning Confocal Microscopy pointed out that the compounds may act by different mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…As a first approach we projected all the 176 compounds on the model previously published [12]. The PLS model after projection of the test set is shown in Figure 1: the predicted compounds are colored according to the different belonging classes: pyrrolopyrimidindione in green, pyrimidinketones in yellow, benzyloxyindole in light blue, indole in red, LCAPs in purple, quinoline in blu, and thiophene in white.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first approach we projected all the 176 compounds on the model previously published [12]. The PLS model after projection of the test set is shown in Figure 1: the predicted compounds are colored according to the different belonging classes: pyrrolopyrimidindione in green, pyrimidinketones in yellow, benzyloxyindole in light blue, indole in red, LCAPs in purple, quinoline in blu, and thiophene in white.…”
Section: Resultsmentioning
confidence: 99%
“…These premises prompted us to design and synthesize novel compounds with high efficacy and specificity for the treatment of breast tumors. In 2013, this research group reported the design and synthesis of new heterocyclic compounds [12]. To fasten the lead discovery process, a Volsurf+ (VS+) model was constructed using a dataset of 59 compounds able to predict the in vitro antitumor activity against MCF-7 cancer cell line for the new derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In total VolSurf plus uses 128 descriptors [46e48]; iii) finally, chemometric tools (PCA [49], PLS [50,51]) are used to create relationships of the VolSurf plus descriptor matrix with ADME properties. The scheme of the VolSurf plus programme steps and a detailed definition of Volsurf plus descriptors have recently been reported [52].…”
Section: Volsurf Plus Descriptorsmentioning
confidence: 99%
“…6,7 Dedicated PPs for amino acids were then derived for peptides QSARs 8 and for quantitative sequence-activity modelling. 12 More recently MIF (Molecular Interaction Field) molecular descriptors 9,[13][14][15][16] were used for ligand-based virtual screening in antitumor drug design. PPs were also derived for Ionic Liquids (ILs), low melting point salts comprising an organic cation and an inorganic or organic anion, which exhibited unprecedented efficiency at a molecular level providing opportunities for the development of green and sustainable chemical procedures.…”
Section: Introductionmentioning
confidence: 99%